2021
DOI: 10.1038/s41398-020-01152-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of influence of the glutamatergic concentration of [18F]FPEB binding to metabotropic glutamate receptor subtype 5 with N-acetylcysteine challenge in rats and SRM/PET study in human healthy volunteers

Abstract: Altered glutamate signaling is thought to be involved in a myriad of psychiatric disorders. Positron emission tomography (PET) imaging with [18F]FPEB allows assessing dynamic changes in metabotropic glutamate receptor 5 (mGluR5) availability underlying neuropathological conditions. The influence of endogenous glutamatergic levels into receptor binding has not been well established yet. The purpose of this study was to explore the [18F]FPEB binding regarding to physiological fluctuations or acute changes of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Another mGluR5 imaging agent, [ 18 F]FPEB, was discovered in preclinical research to have promising imaging characteristics for progression in human trials. Additional research revealed that [ 18 F]FPEB retained in the human brain followed a pattern similar to that of [ 11 C]ABP68 (Dupont et al, 2021). According to research, [ 11 C]ABP‐688 is recommended for drug challenge experiments aiming to describe glutamate neurotransmission, as [ 18 F]FPEB binding was found to be less responsive to rises in extracellular glutamate generated by ketamine injection.…”
Section: Methodsmentioning
confidence: 82%
“…Another mGluR5 imaging agent, [ 18 F]FPEB, was discovered in preclinical research to have promising imaging characteristics for progression in human trials. Additional research revealed that [ 18 F]FPEB retained in the human brain followed a pattern similar to that of [ 11 C]ABP68 (Dupont et al, 2021). According to research, [ 11 C]ABP‐688 is recommended for drug challenge experiments aiming to describe glutamate neurotransmission, as [ 18 F]FPEB binding was found to be less responsive to rises in extracellular glutamate generated by ketamine injection.…”
Section: Methodsmentioning
confidence: 82%
“…We may associate this effect with different mechanisms in previous studies on NAC [11,13,[32][33][34]. One of the prominent mechanisms in the occurrence of the anticonvulsant effect of NAC is the modulation of glutaminergic neurotransmission [8, 12,35]. It has been shown by previous studies that NAC participates in the function of maintaining extrasynaptic non-vesicular glutamate homeostasis.…”
Section: Discussionmentioning
confidence: 89%
“…We may associate this effect with different mechanisms in previous studies on NAC [11,13,[32][33][34]. One of the prominent mechanisms in the occurrence of the anticonvulsant effect of NAC is the modulation of glutaminergic neurotransmission [8, 12,35]. It has been shown by previous studies that NAC participates in the function of maintaining extrasynaptic non-vesicular glutamate homeostasis.…”
Section: Discussionmentioning
confidence: 89%